Development of Student Worksheets (E-LKPD) to Strengthen Numeracy Literacy on Relations and Functions Material - Cahyani, Icha; Fitrianti, Yuli; Nizar, Harisman (Universitas Veteran Bangun Nusantara, 2025)
This study aimed to develop an Electronic Student Worksheet (E-LKPD) that is valid, practical, and has the potential to strengthen numeracy literacy on the topic of relations and functions. The type of research used was Design Research with a development study type that was divided into two stages, namely the preliminary stage and the prototyping stage with formative evaluation that included self evaluation, expert review, one-to-one, small group, and field test. The material used in the E-LKPD was relations and functions. Data collection techniques consisted of questionnaires, interviews, tests, and documentation. The questionnaires consisted of validity and practicality questionnaires. Validity data was obtained from the validity questionnaire which was analyzed quantitatively, while validator comments and suggestions were analyzed qualitatively. Practicality data was obtained through interviews and practicality questionnaire which were analyzed qualitatively and quantitatively at the one-to-one, small group, and field test stages. Meanwhile, potential effect data was obtained from student evaluation tests at the field test stage. The subjects of this study were eighth-grade students at SMP Negeri 7 Palembang. The result of the study showed that the developed E-LKPD was very valid, with an average validity percentage of 88.37%. The E-LKPD was also classified as practical with an average practicality percentage of 73.56%. Furthermore, the potential effect of the E-LKPD in strengthening students’ numeracy literacy on the topic of relation and function was classified as moderate, with an average value of 70.63. This indicate that the developed E-LKPD had a potential effect to strengthen numeracy literacy on the topic of Relation and Functions.